International Journal of Bipolar Disorders - Bauer, Michael
The International Journal of Bipolar Disorders is a peer-reviewed, open access online journal publishing contributions from the broad range of clinical, psychological and biological research in bipolar disorders. It is the official journal of the ECNP-ENBREC (European Network of Bipolar Research Expert Centres) Bipolar Disorders Network, the International Group for the study of Lithium Treated Patients (IGSLi) and the Deutsche Gesellschaft für Bipolare Störungen (DGBS) and invites clinicians and researchers from around the globe to submit original research articles, short research communications, reviews, guidelines, case reports and letters to the editor that help to enhance understanding of bipolar disorders. The International Journal of Bipolar Disorders makes all articles freely available to researchers worldwide, ensuring maximum dissemination of content. Content is published online continuously to provide timely communication to the community and keep publication times to a minimum.